(untitled) (Global Journals of Research in Engineering, 2024)
The analysis of the methodological principles on which pyrometry is based is carried out Special attention is paid to the main methodological postulate and its consequences The roots of its formation are considered It is shown that the large methodological errors characteristic of pyrometry are a direct consequence of the system of priorities arising from this postulate A new basic methodological postulate of pyrometry is formulated it is shown that the development of the ideas contained in it will reduce the number of methodological errors by an order of magnitude or more and the necessary and sufficient conditions for this reduction are formulated